Bilayer electrified-membrane with pair-atom tin catalysts for near-complete conversion of low concentration nitrate to dinitrogen - Xuanhao Wu; Xiaoxiong Wang; Yunshuo Wu; Huimin Xu; Zhe Li; Rongrong Hong; Kali Rigby; Zhongbiao Wu; Jae-Hong Kim (Nature Communications)
Abstract Discharge of wastewater containing nitrate (NO3 −) disrupts aquatic ecosystems even at low concentrations. However, selective and rapid reduction of NO3 − at low concentration to dinitrogen (N2) is technically challenging. Here, we present an electrified membrane (EM) loaded with Sn pair-atom catalysts for highly efficient NO3 − reduction to N2 in a single-pass electrofiltration. The pair-atom design facilitates coupling of adsorbed N intermediates on adjacent Sn atoms to enhance N2 selectivity, which is challenging with conventional fully-isolated single-atom catalyst design. The EM ensures sufficient exposure of the catalysts and intensifies the catalyst interaction with NO3 − through mass transfer enhancement to provide more N intermediates for N2 coupling. We further develop a reduced titanium dioxide EM as the anode to generate free chlorines for fully oxidizing the residual ammonia (<1 mg-N L−1) to N2. The sequential cathode-to-anode electrofiltration realizes near-complete removal of 10 mg-N L−1 NO3 − and ~100% N2 selectivity with a water resident time on the order of seconds. Our findings advance the single-atom catalyst design for NO3 − reduction and provide a practical solution for NO3 − contamination at low concentrations.